2016
DOI: 10.1163/18725465-00901007
|View full text |Cite
|
Sign up to set email alerts
|

Transnational Baye-fallism

Abstract: This article examines the transformation of the Baye-fall movement (Baye-fallism, henceforth), a particular form of Senegalese Muridism, as it extends into the Senegalese diaspora. In particular, the article explores shifts in understandings of what it means to be a ‘good’ Baye-fall, as Senegalese migrants in Spain become confronted with hostility in their new social context, and as the need for spiritual engagement and community belonging intensifies. Starting with the origins of Baye-fallism as a Sufi hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…In some studies, the elicitation of positive emotions was reported as enhancing self-reflection and a critical self-awareness for CYP defined as at-risk or offending. Participants were reported as being able to redefine a more (self) caring and accepting sense of identity that challenged and resisted established and negative mindsets through learning new skills and achieving successful arts-related outcomes (Atherton, 2022;Clennon, 2015;Gann, 2010;Hanrahan, 2017;Massó-Guijarro, 2020;Morgan, 2020;Nicklin, 2017;Parker, 2018;Tett, 2012;Thompson, 2015;Winn, 2010Winn, , 2011. It was suggested by study authors that such processes of self-determination could enable experiences of autonomy and empowerment through participation in art activities (Hickey, 2018;Lotter, 2015;Pope, 2022).…”
Section: Positive Emotional Experiences Of Arts-based Interventions G...mentioning
confidence: 99%
See 4 more Smart Citations
“…In some studies, the elicitation of positive emotions was reported as enhancing self-reflection and a critical self-awareness for CYP defined as at-risk or offending. Participants were reported as being able to redefine a more (self) caring and accepting sense of identity that challenged and resisted established and negative mindsets through learning new skills and achieving successful arts-related outcomes (Atherton, 2022;Clennon, 2015;Gann, 2010;Hanrahan, 2017;Massó-Guijarro, 2020;Morgan, 2020;Nicklin, 2017;Parker, 2018;Tett, 2012;Thompson, 2015;Winn, 2010Winn, , 2011. It was suggested by study authors that such processes of self-determination could enable experiences of autonomy and empowerment through participation in art activities (Hickey, 2018;Lotter, 2015;Pope, 2022).…”
Section: Positive Emotional Experiences Of Arts-based Interventions G...mentioning
confidence: 99%
“…Twenty-four studies used only one qualitative method for data collection. Of these, 11 employed ethnographic observation methods (Baker, 2007;Clennon, 2015;Gann, 2010;Massó-Guijarro, 2020;Podkalicka, 2009;Winn, 2010Winn, , 2011Zlotowitz, 2016). One study used auto ethnography (Thompson, 2015).…”
Section: Qualitative Studiesmentioning
confidence: 99%
See 3 more Smart Citations